Diet, nutrition, and climate: historical and contemporary connections - Kathrin M. Demmler; M. Ann Tutwiler (Frontiers in Nutrition)
This paper reviews the past global nutrition efforts, particularly those led by the Global Alliance for Improved Nutrition (GAIN), at the critical intersection of nutrition and climate change. Despite progress in tackling malnutrition and promoting sustainable food systems, significant challenges remain, especially in regions like Sub-Saharan Africa and South Asia, where micronutrient deficiencies persist. The paper underscores the urgent need to integrate nutrition into climate strategies and strengthen food system resilience. Initiatives like the Scaling Up Nutrition (SUN) movement, the Food Systems Dashboard, and GAIN’s public and private sector partnerships at the local levels have contributed to transforming food systems. However, there is an urgent need for more robust policies that effectively align nutrition, climate, and equity goals. Looking ahead, we advocate for increased financial investment, improved policy frameworks, and innovations in technology and data monitoring to drive sustainable food system transformations. We further underscore the importance of addressing micronutrient deficiencies, promoting biodiversity, and developing healthier crops to support climate-smart agriculture. Achieving resilient, equitable, and sustainable food systems over the next years will depend on collaborative efforts across sectors and stakeholders.